saudi Arabia- making friends, making enemies. - BAIRD, VANESSA (New Internationalist, 2016)
An introduction is presented in which the editor discusses various reports within the issue on topics including views of computer programmer Julian Assange on Saudi regime, orphanage scam in Nepal, and Turkey president Recep Tayyip Erdoğan.